The special account procedure as a technique of central bank control. A study of fifteen years of Australian experience - ARNDT, H.W. (PSL Quarterly Review, 2014)
The article assesses the merits of the Special Account procedure as a central banking technique in the light of a detailed study of the Commonwealth Bank’s special account policy over this period. The author finds that the Special Account procedure has proved to be a powerful and flexible instrument which has, for the first time, given the Australian central bank adequate control over trading bank liquidity. But the appropriate use of special accounts in the difficult conditions of almost continuous inflationary pressure has been no easy task. The Commonwealth Bank has experimented with a variety of special account policies, including an unsuccessful attempt to operate on the basis of voluntary adherence by the trading banks to conventional liquid asset ratios. Its most recent policy appears to assimilate special accounts closely to the New Zealand Reserve Bank’s use of variable minimum reserves to keep trading bank liquidity at low levels but relieve pressure by central bank loans at penal rates. JEL: E52, E58